زكاة النفط والغاز: دراسة فقهية مقاصدية - شعرانة، محمد (al-Jami'ah al-Islamiyah al-'Alamiyah, 2017)
This is an analytical study of the legality of the Zakah on oil and gas. This study begins with elucidating the nature of oil and gas and their similarity with the “Zakah wealth” by adopting inductive method in gathering all the relevant information from the texts, evidences and the opinions of early and contemporary jurists as well as critically analysing the evidence. The third chapter discusses the ownership of oil and gas and the legality of their Zakah in light of the Maqasid of wealth by analysing the opinions of jurists. According to the preponderant view, Zakah is obligatory on every extracted thing from the Earth, whether it is State property or private property such as franchise companies. It serves the public interest and is in accordance with the higher objectives of Islam and Muslims. The principle adopted to reach this conclusion is: “Every form of wealth which incurs development and trade is applicable for Zakah”. In the fourth chapter, the researcher have adopted the opinion that Zakah should be given to other countries if the country which extracts it is self sufficient and the channels of Zakah disbursement were also discussed in the light of the Maqasid of Zakah. The main conclusions of this thesis can be summarized in some points: when the state property which includes oil and gas is invested, Zakah becomes obligatory on it. Additionally, the contracts with foreign companies, which are in the interest of Muslims, must have some rules and regulations in case of dire necessity. It is a priority to address contemporary issues related to Zakah like the legality of Zakah on oil and gas and how they could help reach a unified opinion on the global level which fulfills the Maqasid of Zakah and its application in protecting Muslim wealth and making the Ummah self-sufficient.